Comparison of medical-grade and calibrated consumer-grade displays for diagnosis of subtle bone fissures. - Pinto dos Santos, Daniel; Welter, Jonas; Emrich, Tilman; Jungmann, Florian; Dappa, Evelyn; Mildenberger, Peter; Kloeckner, Roman (European Radiology, 2017)
Objective: To compare the diagnostic accuracy of medical-grade and calibrated consumer-grade digital displays for the detection of subtle bone fissures.Methods: Three experienced radiologists assessed 96 digital radiographs, 40 without and 56 with subtle bone fissures, for the presence or absence of fissures in various bones using one consumer-grade and two medical-grade displays calibrated according to the DICOM-Grayscale Standard Display Function. The reference standard was consensus reading. Subjective image quality was also assessed by the three readers. Statistical analysis was performed using receiver operating characteristic analysis and by calculating the sensitivity, specificity, and Youden's J for each combination of reader and display. Cohen's unweighted kappa was calculated to assess inter-rater agreement. Subjective image quality was compared using the Wilcoxon signed-rank test.Results: No significant differences were found for the assessment of subjective image quality. Diagnostic performance was similar across all readers and displays, with Youden's J ranging from 0.443 to 0.661. The differences were influenced more by the reader than by the display used for the assessment.Conclusion: No significant differences were found between medical-grade and calibrated consumer-grade displays with regard to their diagnostic performance in assessing subtle bone fissures. Calibrated consumer-grade displays may be sufficient for most radiological examinations.Key Points: • Diagnostic performance of calibrated consumer-grade displays is comparable to medical-grade displays. • There is no significant difference with regard to subjective image quality. • Use of calibrated consumer-grade displays could cut display costs by 60-80%.